Export, foreign direct investment, and joint ventures: Learning the rival's costs through propinquity - Anthony Creane; Kaz Miyagiwa (Osaka University, Institute of Social and Economic Research (ISER), 2007)
We examine the role of cost uncertainty in a firm's choice between exporting and foreign investment in oligopolistic industry. We consider both foreign direct investment and an international joint venture, and allow country-specific and firm-specific cost uncertainty. Unlike exporting, either form of foreign investment exposes home and foreign firms to common country-specific cost shocks, implying a better knowledge of each other's country-specific shocks. Further, a joint venture allows the firms to learn each other's firm-specific cost. A firm's plant location decision depends on the interaction of these two effects, which depend on the type of competition and the substitutability of the firm's products.
Keywords: D83; F12; 330; Country-specific cost uncertainty; learning; Foreign investment; FDI; Joint ventures; Internationale Geschäftsbeziehungen; Export; Auslandsinvestition; Joint Venture; Strategisches Management; Kostenanalyse; Theorie